THE ROLE OF THE STATE IN BUILDING A SUSTAINABLE NATIONAL IDENTITY: CASE STUDY OF MEXICO - Lazić, Nikola (Political Review, 2023)
This research investigates the national identity building process and corresponding role of the state in it. In many societies, states monopolised entire process, yet success they have been achieving is ambiguous. Using the Mexico case study, the research explores prospects of the state to lead the process of building a stable and sustainable national identity. To respond to the research question, authors analyse role of the Mexican state and ruling regimes in the process of different narratives production and parallelly investigates structural, historically conditioned factors. The conclusion is that the state cannot compensate authenticity and stability of the national identities which arise independently through the longue durée processes by producing and imposing artificial discourses and ideas.